2016
DOI: 10.1016/j.jconrel.2016.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Controlling levonorgestrel binding and release in a multi-purpose prevention technology vaginal ring device

Abstract: Despite a long history of incorporating steroids into silicone elastomers for drug delivery applications, little is presently known about the propensity for irreversible drug binding in these systems. In this study, the ability of the contraceptive progestin levonorgestrel to bind chemically with hydrosilane groups in addition-cure silicone elastomers has been thoroughly investigated. Cure time, cure temperature, levonorgestrel particle size, initial levonorgestrel loading and silicone elastomer type were demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 29 publications
5
36
1
Order By: Relevance
“…The DPV+LNG slab samples cured under the same conditions as the DDU-4320 product specification provided a value of 11.50  0.55 Shore A. In this case, the lower durometer value may be attributable to inhibition of the silicone elastomer curing reaction as a result of irreversible covalent binding of the LNG molecules to the addition-cure silicone elastomer system (Murphy et al, 2016).…”
Section: Durometer Hardness Testmentioning
confidence: 99%
“…The DPV+LNG slab samples cured under the same conditions as the DDU-4320 product specification provided a value of 11.50  0.55 Shore A. In this case, the lower durometer value may be attributable to inhibition of the silicone elastomer curing reaction as a result of irreversible covalent binding of the LNG molecules to the addition-cure silicone elastomer system (Murphy et al, 2016).…”
Section: Durometer Hardness Testmentioning
confidence: 99%
“…Various release media have been used for in vitro release testing of dapivirinereleasing rings during the past twelve years of development, including simulated vaginal fluid (SVF; a substantially aqueous, non-buffered medium), various buffer systems, aqueous media incorporating surfactant(s), and various organic solvent/water mixtures (Fetherston et al, 2013a(Fetherston et al, , 2013bMalcolm et al, 2005;R. Karl Malcolm et al, 2012;Murphy et al, 2016aMurphy et al, , 2016bMurphy et al, , 2014Woolfson et al, 2006). SVF is unquestionably the most physiologic medium here, but it affords very low in vitro release of dapivirine (in the order of low micrograms per day) even when relatively large volumes (> 100 mL) are used, due to the poor aqueous solubility of dapivirine.…”
Section: In Vitro Release From Matrix-type Vaginal Ringsmentioning
confidence: 99%
“…Koetsawang et al, 1990aS. Koetsawang et al, , 1990bMishell et al, 1975;Murphy et al, 2016b). Recently, as part of continued efforts to develop a MPT vaginal ring offering simultaneous release of DPV and LNG, we reported on various formulation strategies to reduce the extent of LNG binding to addition cure silicone elastomer materials (Murphy et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low dose LNG rings had been used previously in studies conducted by WHO and were shown to be effective in women who weighed less than 80 kg but had higher failure rates in higher weight women (43). The current design of the Dapivirine/LNG ring is to find a dose of LNG that will inhibit ovulation (44). Early phase clinical studies of the rings are ongoing.…”
Section: Multipurpose Technologiesmentioning
confidence: 99%